2007
DOI: 10.1002/biof.552029201
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐obesity activities of fermented soygerm isoflavones by Bif idobacterium breve

Abstract: Soygerm isoflavones were subjected to fermentation by Bifidobacterium breve. Most of isoflavone glycosides (daidzin, glycitin and genistin) in soygerms were deglycosylated to their corresponding isoflavone aglycones (daidzein, glycitein and genistein) within 24 h fermentation. Fermented isoflavones significantly inhibited pancreatic lipase activity in fermentation-time and dosage dependant manner. When fermented isoflavones were orally administered with olive oil to SD rats, the triglyceride (TG) level in plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 26 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…Recent data showed that the fermented soygerm isoflavones (daidzein, genistein and glycitein) significantly inhibited pancreatic lipase activity in dose-dependent manner, thereby suppressing absorption of excessive lipid into a body. 60 These finding were in consistent with our data that is, increase in fecal TG excretion by daidzein supplementation, even if we did not measure the pancreas lipase activity. The inhibition of pancreas lipase activity can reduce the conversion of TG to monoglyceride or FFA, a final lipid form for absorption, which subsequently can inhibit the lipid absorption.…”
Section: Discussionsupporting
confidence: 91%
“…Recent data showed that the fermented soygerm isoflavones (daidzein, genistein and glycitein) significantly inhibited pancreatic lipase activity in dose-dependent manner, thereby suppressing absorption of excessive lipid into a body. 60 These finding were in consistent with our data that is, increase in fecal TG excretion by daidzein supplementation, even if we did not measure the pancreas lipase activity. The inhibition of pancreas lipase activity can reduce the conversion of TG to monoglyceride or FFA, a final lipid form for absorption, which subsequently can inhibit the lipid absorption.…”
Section: Discussionsupporting
confidence: 91%
“…The chemical shifts of compound a in the 13 C-NMR spectrum (Table 5) agree well with the values recorded in the previous study. 17) Taken together, compound a was identified as kaempferol 3…”
Section: Identification Of the Kaempferol Glycosides From Jindai Soybmentioning
confidence: 99%
“…An effective treatment for type 2 diabetes and the metabolic syndrome as a cause of diabetes would clearly be of great benefit to the individual and society. 3) Flavonoids are polyphenolic compounds widely distributed throughout the plant kingdom. 4) They are important to protect plant leaves from UV rays during their growth.…”
mentioning
confidence: 99%
“…47 Isoflavone aglycones not only are absorbed faster and greater amounts in human body, but it also suppressed absorption of lipid into a body effectively than their glycoside form. [48][49] Secondly, Kim et al 23 demonstrated that L. plantarum P1201 produced higher CLA contents after fermentation of Daewon steamed soybean. Supplementation of CLA has been reported to decrease in body fat via reduction of energy intake, which may reduce body weight gain and prevent obesity.…”
Section: -43mentioning
confidence: 99%